Menggali Intan Berlian di Kubangan Berlumpur: Sebuah Upaya PKBM â€œAnugrah Bangsaâ€ dalam Mengelola Pendidikan bagi Anak Bermasalah (Forum Ilmu Sosial, 2019)
PKBM "Anugrah Bangsa" is one of the homeschooling non-formal education in the Semarang which is sheltered by the Anugrah Nusa Bangsa Indonesia Foundation. The purpose of this study is to find out the PKBM efforts "Anugrah Bangsa" in helping education to troubled children in the city of Semarang and analyzing the obstacles PKBM â€œAnugrah Bangsaâ€ in helping education for troubled child in Semarang. This study uses qualitative methods. Theoretical analysis uses alternative education concepts from Paulo Freire. The results of this study indicate that at the introduction stage the efforts made by PKBM "Anugrah Bangsa" are socialization using social media, print, and community empowerment. At the education management stage efforts are made through the selection of a flexible education system, extracurricular freedom, activities inside and outside the classroom, and the presence of tutors who are like friends for "problem children". These efforts seem to have obstacles in the form of internal barriers and external barriers.